The Use of Raman Spectroscopy to Monitor Metabolic Changes in Stressed Metschnikowia sp. Yeasts - Němcová, Andrea; Gonová, Dominika; Samek, Ota; Sipiczki, Matthias; Breierová, Emilia; Márová, Ivana (Microorganisms, 2021)
Raman spectroscopy is a universal method designed for the analysis of a wide range of physical, chemical and biological systems or various surfaces. This technique is suitable to monitor various components of cells, tissues or microorganisms. The advantages include very fast non-contact and non-destructive analysis and no or minimal need for sample treatment. The yeasts Metschnikowia can be considered as industrially usable producers of pulcherrimin or single-cell lipids, depending on cultivation conditions and external stress. In the present study, Raman spectroscopy was used as an effective tool to identify both pulcherrimin and lipids in single yeast cells. The analysis of pulcherrimin is very demanding; so far, there is no optimal procedure to analyze or identify this pigment. Based on results, the strong dependence of pulcherrimin production on the ferric ion concentration was found with the highest yield in media containing 0.1 g/L iron. Further, production of lipids in Metschnikowia cells was studied at different temperatures and C:N ratios, using Raman spectroscopy to follow fatty acids composition, under different regimes, by monitoring the iodine number. The results of Raman spectroscopy were comparable with the fatty acid analysis obtained by gas chromatography. This study therefore supported use of Raman spectroscopy for biotechnological applications as a simple tool in the identification and analysis both the pulcherrimin and microbial lipids. This method provides a quick and relatively accurate estimation of targeted metabolites with minimal sample modification and allows to monitor metabolic changes over time of cultivation.
Keywords: BF; MF

Use of Waste Substrates for the Lipid Production by Yeasts of the Genus Metschnikowia—Screening Study - Němcová, Andrea; Szotkowski, Martin; Samek, Ota; Cagáňová, Linda; Sipiczki, Matthias; Márová, Ivana (Microorganisms, 2021)
Oleogenic yeasts are characterized by the ability to accumulate increased amounts of lipids under certain conditions. These microbial lipids differ in their fatty acid composition, which allows them to be widely used in the biotechnology industry. The interest of biotechnologists is closely linked to the rising prices of fossil fuels in recent years. Their negative environmental impact is caused by significantly increased demand for biodiesel. The composition of microbial lipids is very similar to vegetable oils, which provides great potential for use in the production of biodiesel. In addition, some oleogenic microorganisms are capable of producing lipids with a high proportion of unsaturated fatty acids. The presented paper’s main aim was to study the production of lipids and lipid substances by yeasts of the genus Metschnikowia, to cultivate crude waste animal fat to study its utilization by yeasts, and to apply the idea of circular economy in the biotechnology of Metschnikowia yeasts. The work focuses on the influence of various stress factors in the cultivation process, such as reduced temperature or nutritional stress through the use of various waste substrates, together with manipulating the ratio of carbon and nitrogen sources in the medium. Yeast production properties were monitored by several instrumental techniques, including gas chromatography and Raman spectroscopy. The amount of lipids and in particular the fatty acid composition varied depending on the strains studied and the culture conditions used. The ability of yeast to produce significant amounts of unsaturated fatty acids was also demonstrated in the work. The most suitable substrate for lipid production was a medium containing glycerol, where the amount of accumulated lipids in the yeast M. pulcherrima 1232 was up to 36%. In our work, the crude animal fat was used for the production of high-value lipids, which to the best of our knowledge is a new result. Moreover, quantitative screening of lipase enzyme activity cultivated on animal fat substrate on selected yeasts of the genus Metschnikowia was performed. We found that for the yeast utilizing glycerol, animal fat seems to be an excellent source of carbon. Therefore, the yeast conversion of crude processed animal fat to value-added products is a valuable process for the biotechnology and food industry.
Keywords: BF; MF

What keeps polyhydroxyalkanoates in bacterial cells amorphous? A derivation from stress exposure experiments - P. Sedláček; Slaninová, E.; Enev, V.; Koller, M.; J. Nebesářová; I. Márová; K. Hrubanová; V. Krzyžánek; O. Samek; S. Obruča (Appl. Microbiol. Biotech., 2019)
Keywords: BF; MF

The presence of PHB granules in cytoplasm protects non-halophilic bacterial cells against the harmful impact of hypertonic environments - S. Obruča; P. Sedláček; F. Mravec; V. Krzyžánek; J. Nebesářová; O. Samek; D. Kučera; Pavla Benešová; K. Hrubanová; M. Milerová; I. Márová (New Biotechnol., 2017)
Keywords: BF; MF

Accumulation of Poly(3-hydroxybutyrate) Helps Bacterial Cells to Survive Freezing - S. Obruča; P. Sedláček; V. Krzyžánek; F. Mravec; K. Hrubanová; O. Samek; D. Kučera; Pavla Benešová; I. Márová (PLoS ONE, 2016)
Keywords: MF

Evaluation of 3-hydroxybutyrate as an enzyme-protective agent against heating and oxidative damage and its potential role in stress response of poly(3-hydroxybutyrate) accumulating cells - S. Obruča; P. Sedláček; F. Mravec; O. Samek; I. Márová (Appl Microbiol Biotechnol, 2016)
Keywords: MF

Morphological and Production Changes in Stressed Red Yeasts Monitored Using SEM and Raman Spectroscopy - K. Hrubanová; O. Samek; A. Haroniková; Silva Bernatová; P. Zemánek; I. Márová; V. Krzyžánek (Microscopy and Microanalysis, 2016)
Keywords: MF

Quantitative Raman Spectroscopy Analysis of Polyhydroxyalkanoates Produced by Cupriavidus necator H16 - O. Samek; S. Obruča; M Šiler; P. Sedláček; Pavla Benešová; D. Kučera; I. Márová; J Ježek; Silva Bernatová; P. Zemánek (Sensors, 2016)
Keywords: MF

Cryo-SEM and Raman Spectroscopy Study of the Involvement of Polyhydroxyalkanoates in Stress Response of Bacteria - V. Krzyžánek; K. Hrubanová; O. Samek; S. Obruča; I. Márová; Silva Bernatová; M Šiler; P. Zemánek (Microscopy and Microanalysis, 2015)
Keywords: MF

SEM and Raman Spectroscopy Applied to Biomass Analysis for Application in the Field of Biofuels and Food Industry - O. Samek; A. Haroniková; N. Vaškovicová; K. Hrubanová; J Ježek; I. Márová; V. Krzyžánek; P. Zemánek (Microscopy and Microanalysis, 2015)
Keywords: MF